Multi-objective cooperative coevolution algorithm with a Master–Slave mechanism for Seru Production - Li, Xiaolong; Yu, Yang; Huang, Min (Applied soft computing, 2022)
Seru Production is usually used as a creative mode of production in electronics. It involves two NP-hard subproblems, namely seru formation and seru scheduling. To obtain the optimal global solution of multi-objective Seru Production, we develop a multi-objective cooperative coevolution algorithm with a Master–Slave mechanism. In the proposed algorithm, a cooperative mechanism is used to simultaneously optimize seru formation and seru scheduling. In addition, three usually non-dominated solutions are defined and used in the cooperative mechanism to improve the quality of non-dominated solutions, which takes more computational time. To reduce the computational time, three seru scheduling/seru formation populations evolve in parallel with the assistance of the three corresponding non-dominated seru formations/seru schedulings. To further improve the quality of non-dominated solutions, we propose a Master–Slave​ mechanism. The Master population is designed to store the current non-dominated solutions and communicates with three Slave populations. Extensively tested experiments show that the proposed algorithm outperforms existing algorithms for multi-objective Seru Production. •Seru Production has been widely used in the electronics industry.•Three usually non-dominated solutions are used in the cooperative mechanism to improve the non-dominated solutions.•To reduce computational time, three Slave populations evolve in parallel.•The Master–Slave mechanism is developed to improve the quality of non-dominated solutions.